2021
DOI: 10.3390/molecules26051201
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant Activity, and Cytotoxicity Assessment of Tagetes erecta L. Flowers

Abstract: Tagetes erecta L. is a popular ornamental plant of the Asteraceae family, which is widely cultivated not only for its decorative use, but also for the extraction of lutein. Besides carotenoid representatives, which have been extensively studied, other important classes of secondary metabolites present in the plant, such as polyphenols, could exhibit important biological activities. The phytochemical analysis of a methanolic extract obtained from T. erecta inflorescences was achieved using liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
(21 reference statements)
0
32
0
Order By: Relevance
“…The 15-LOX inhibition capacity of extracts and of their corresponding AgNPs was evaluated using the modified Malterud method [9,29]. In total, 50 µL lipoxidase from Glycine max in borate buffer (pH 9) and 50 µL of the sample/control solution were mixed and then left to stand for 10 min.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The 15-LOX inhibition capacity of extracts and of their corresponding AgNPs was evaluated using the modified Malterud method [9,29]. In total, 50 µL lipoxidase from Glycine max in borate buffer (pH 9) and 50 µL of the sample/control solution were mixed and then left to stand for 10 min.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…The present paper investigates the synthesis of silver nanoparticles using green chemistry and their characterization. For the synthesis of nanoparticles using biological methods, we chose Tagetes erecta (T. erecta), an ornamental plant very common in most geographical areas, taking into consideration its availability, as well as the fact that the species has been intensively studied regarding its chemical composition [9]. The species is a popular plant found in the Asteraceae family and it is widely cultivated for its decorative properties, as well as for the extraction of carotenoids [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plate was incubated at 37 °C, 5%CO2 for 24h and the cells viability was measured by using the MTT assay as described previously (20). The yellow-colored MTT was reduced by the mitochondrial succinate dehydrogenase of active living cells to purple formazan which the optical density can be measured at 570 nm 16 . At the end of the incubation period, the supernatant was aspirated from the wells of the plate and 100 μL of the MTT solution (5 mg / mL in HBSS buffer) was added.…”
Section: Cytoprotection Studymentioning
confidence: 99%
“…Pharmacological properties of rutin include anti-inflammation 8 , antioxidant 9 , anti-physical fatigue 10 , antidiabetic and anticancer 7 as well as neuroprotective 11 and cardioprotective agent 12 . Previous biological investigations demonstrated that rutin increases antioxidant enzymes, catalase, superoxide dismutase, glutathione peroxidase, and glutathione level in rat PC-12 cells and prevents cells damages induced by a neurotoxic agent, 6-hydroxydopamine 16 . Moreover, rutin restored memory in doxorubicin-induced memory deficits in rat .…”
Section: Introductionmentioning
confidence: 96%